(untitled) (Singapore, 2017)
Principles of Marketing courses that require a comprehensive text. Help students learn how to create value through customer connections and engagementIn a fast-changing, increasingly digital and social marketplace, it's more vital than ever for marketers to develop meaningful connections with their customers. The Principles of Marketing, An Asian Perspective provides an authoritative, comprehensive, innovative, managerial, and practical introduction to the fascinating world of marketing in and from Asia. It helps students master today's key marketing challenge: to create vibrant, interactive communities of consumers in Asia who make products and brands an integral part of their daily lives. To help students in Asia understand how to create value and build customer relationships, the Asian Perspective presents fundamental marketing information within an innovative customer-value framework. This textbook makes learning about and teaching Asian marketing easier and more exciting for both students and instructors by providing a variety of vignettes, up-to-date corporate examples, and relevant case studies.
Keywords: Tiếp thị,Marketing; Châu Á,Asia